Simulation of Torsional Vibration of Driven Railway Wheelsets Respecting the Drive Control Response on the Vibration Excitation in the Wheel-Rail Contact Point - Trimpe, Fritz; Lück, Sönke; Naumann, Rolf; Salander, Corinna (Vibration)
For the stability verification of railway wheelsets in Germany, dynamic torsional stresses must be respected as they affect the axle and press fit stability of a wheelset. These dynamic stresses are applied to a wheelset by torsional vibration. However, dynamic stresses cannot be predicted by calculation, and so time-consuming and cost-intensive test runs are performed to measure the maximum dynamic stresses. Therefore, this article deals with the setup of a simulation model that shall enable the simulative prediction of maximum dynamic torsional stresses. This model respects that vibration excitation originates from the wheel-rail contact point and that the vibration energy input comes from a high-frequency drive train control. The first results show successful simulation of vibration excitation and correlations between adhesion change and maximum dynamic stresses.